Evaluation of the Applications of Contemporary Facilities Management in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study was aimed at evaluating the applications of contemporary Facilities Management in Nigeria in order to encourage massive adoption over traditional approach. Its objectives range from identifying the applications of both traditional and contemporary Facilities Management practices in Nigeria, to identifying the benefit and challenges of the Modern/contemporary practices over the older form of facility management. Traditional approach to facility management has been proved to be unsuitable and ineffective in the 21st century and at such this independent studies paper seeks to encourage the wide adoption of contemporary facilities management due to its prevailing benefits, added is numerous recommendations to challenges that it may also present since the practice is seemly new in Nigeria. Contemporary practices in facility management in Nigeria which encompasses software and mobile applications have been created to ease facility management in the modern age. Several of such application and mobile software’s were discussed and extensively discussed and un-discussed ones are available for further research.